Answer:
1. The other root is
![-2](https://img.qammunity.org/2020/formulas/mathematics/high-school/fidm7xkkuyojp2ex8ijz9c0p1ybj5j4f4i.png)
2. c=-106
Explanation:
The given equation is
.
If
is a solution to the given quadratic equation, then
must satisfy this equation.
![10(5.3)^2-33(5.3)+c=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/4nf57fkxhiubufl1ptcqvbcum5zwpbnpbu.png)
![280.9-174.9+c=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/bg3pn7lv5d4nqn04fu01wyd4lk9ahv3v3m.png)
![106+c=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/hm72aj85lw9hj9h2lt5n223zy3j44xjafo.png)
![c=0-106=-106](https://img.qammunity.org/2020/formulas/mathematics/middle-school/hn1s8tp6z9vfe4x3t5cycexatvxr8zdl9q.png)
We now substitute
into the given equation to obtain;
.
Comparing to the general equation;
, we have a=10, b=-33 and c=-106.
Recall the quadratic formula;
![x=(-b\pm √(b^2-4ac) )/(2a)](https://img.qammunity.org/2020/formulas/mathematics/high-school/e7vfp9bwgt0u5jzem3ndaljl3t2agny4bk.png)
We now use the quadratic formula to obtain;
![x=(--33\pm √((-33)^2-4(10)(-106)) )/(2(10))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/qtuzr6gz4vs3whm65ye4sk84v8lj7h9nkm.png)
This implies that;
![x=(33\pm √(5329) )/(20)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/4la15kwwubrea2r2fm9l6h771wm6f4qcnt.png)
![x=(33\pm73)/(20)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/geq45hq5xlj35asrp0fgteokkdk59c2kwt.png)
or
or
or
Hence the other root is
![-2](https://img.qammunity.org/2020/formulas/mathematics/high-school/fidm7xkkuyojp2ex8ijz9c0p1ybj5j4f4i.png)